If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2X + 85) = 0 Reorder the terms: (85 + 2X) = 0 Remove parenthesis around (85 + 2X) 85 + 2X = 0 Solving 85 + 2X = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-85' to each side of the equation. 85 + -85 + 2X = 0 + -85 Combine like terms: 85 + -85 = 0 0 + 2X = 0 + -85 2X = 0 + -85 Combine like terms: 0 + -85 = -85 2X = -85 Divide each side by '2'. X = -42.5 Simplifying X = -42.5
| 4x+11+6x=2+x-9 | | x(9x-7)=(9x+8)(x-3) | | 4x+8x+11y+2w+3x-2y= | | k(k)=y | | 5x=4+-.1y | | 0=56+7x | | 0.16(18x+30)-8x= | | 4x-7w= | | 13s-234=3s-14 | | 10a-2b=-26 | | 2(9+x)=-15(4+x) | | -6=h/18 | | (7x-6)=6-7x | | 5x+17=5x+98 | | X^3-48=4x | | 30+8n=4(2n+7) | | x=2x-73 | | m+1.89=6.519 | | 7(x+4)=3(x+2) | | -6(1+7k)-5=-4K+27 | | -3t+6=60 | | 9p+5=-12 | | 3-5*4= | | -(6x+8)=-8-6x | | 8.2x=10.66 | | -5x+2x=-12 | | 4x+x-3=2 | | 0.3(x+20)-0.05(x-10)=21.5 | | g(x)=17x^9+1 | | y=5x+150 | | (17x-7)+20x+15x+(12x-17)=360 | | 24+4b=6(b+2) |